Prospective international multicenter study on endoscopic ultrasound-guided biliary drainage for patients with malignant distal biliary obstruction after failed endoscopic retrograde cholangiopancreatography - Khashab, Mouen A.; Van der Merwe, Schalk; Kunda, Rastislav; El Zein, Mohamad H.; Teoh, Anthony Y.; Marson, Fernando P.; Fabbri, Carlo; Tarantino, Ilaria; Varadarajulu, Shyam; Modayil, Rani J.; Stavropoulos, Stavros N.; Peñas, Irene; Ngamruengphong, Saowanee; Kumbhari, Vivek; Romagnuolo, Joseph; Shah, Raj; Kalloo, Anthony N.; Perez-Miranda, Manuel; Artifon, Everson L. (Endoscopy International Open, 2016)
Background and aims: Endoscopic ultrasound-guided biliary drainage (EUS-BD) has emerged as an alternative to traditional radiologic and surgical drainage procedures after failed endoscopic retrograde cholangiopancreatography (ERCP). However, prospective multicenter data are lacking. The aims of this study were to prospectively assess the short- and long-term efficacy and safety of EUS-BD in patients with malignant distal biliary obstruction.Patients and methods: Consecutive patients at 12 tertiary centers (5 US, 5 European, 1 Asian, 1 South American) with malignant distal biliary obstruction and failed ERCP underwent EUS-BD. Technical success was defined as successful stent placement in the desired position. Clinical success was defined as a reduction in bilirubin by 50 % at 2 weeks or to below 3 mg/dL at 4 weeks. Adverse events were prospectively tracked and graded according to the American Society for Gastrointestinal Endoscopy (ASGE) lexicon’s severity grading system. Overall survival and duration of stent patency were calculated using Kaplan–Meier analysis.Results: A total of 96 patients (mean age 66 years, female 45 %, pancreatic cancer 55 %) underwent EUS-BD. Stent placement (technical success) was achieved in 92 (95.8 %) patients (metallic stent 84, plastic stent 8). Mean procedure time was 40 minutes. Clinical success was achieved in 86 (89.5 %) patients. A total of 10 (10.5 %) adverse events occurred: pneumoperitoneum (n = 2), sheared wire (n = 1), bleeding (n = 1), bile leak (n = 3), cholangitis (n = 2), and unintentional perforation (n = 1); 4 graded as mild, 4 moderate, 1 severe, and 1 fatal (due to perforation). A total of 38 (44 %) patients died of disease progression during the study period. The median patient survival was 167 days (95 %CI 112 – 221) days. The 6-month stent patency rate was 95 % (95 %CI 94.94 – 95.06 %) and the 1-year stent patency was 86 % (95 %CI 85.74 – 86.26 %).Conclusion: This study on EUS-BD demonstrates excellent efficacy and safety of EUS-BD when performed by experts.Study registration: NCT01889953